Adrenal abscess in a 3-week-old neonate – a case report - Rumińska, Małgorzata (J Ultrason, 2015)
The authors present a case of a 6-year-old boy operated on in the 4th week of life because of adrenal abscess. The diagnosis of an adrenal abscess in the neonatal period is challenging due to its rare occurrence and non-specific signs. Adrenal abscesses can develop via two mechanisms: as a result of a hematogenic infection and a spread of bacteria to “normal” adrenal glands or, which is much more common, a complication of an adrenal hematoma. Early and accurate diagnosis is crucial for appropriate therapeutic management. Imaging, including ultrasound, can be problematic. The final diagnosis is frequently established on the basis of a histological examination of a surgical specimen.